Dropped in Without a Parachute: Library Managers' Supervision Experiences. Issue 7 (3rd October 2017) - Funge, Simon P.; Robinson-Nkongola, Audrey; DeLancey, Laura; Griffiths, Austin
ABSTRACT: A survey of U.S. library managers explored the relationship between their social identities, experiences supervising others, support from others, and their overall satisfaction in their professional role. The literature provides evidence that demographic differences give rise to challenges in the workplace. Though no statistically significant differences were found between minority and nonminority managers related to supervisees' microaggressive behaviors, written commentary provided evidence of these and other supervision challenges. A regression analysis found that supervisees' behaviors, along with a manager's age, were significant predictors of their satisfaction as a supervisor. Recommendations for further research and implications for libraries emerge from these findings.